ECONOMIC DEVELOPMENT IN AFRICA AND EUROPE: RECIPROCAL COMPARISONS*. (16th December 2015) - Broadberry, Stephen; Gardner, Leigh
ABSTRACT: Recent advances in historical national accounting have allowed for global comparisons of GDP per capita across space and time. Critics have argued that GDP per capita fails to capture adequately the multi-dimensional nature of welfare, and have developed alternative measures such as the human development index. Whilst recognising that these wider indicators provide an appropriate way of assessing levels of welfare, we argue that GDP per capita remains a more appropriate measure for assessing development potential, focussing on production possibilities and the sustainability of consumption. Twentieth-century Africa and pre-industrial Europe are used to show how such data can guide reciprocal comparisons to provide insights into the process of development on both continents. RESUMEN: Los avances recientes en la historia de la contabilidad nacional han permitido comparaciones globales del PIB per cápita a través de espacio y tiempo. Los críticos de este enfoque han argumentado que el PIB per cápita no capta adecuadamente la naturaleza multidimensional del bienestar, y han desarrollado medidas alternativas tales como el índice de desarrollo humano (IDH). Si bien se reconoce que estos indicadores más amplios proporcionan una forma adecuada de evaluar los niveles de bienestar, en este trabajo sostenemos que el PIB per cápita sigue siendo una medida más apropiada para evaluar el potencial de desarrollo, centrándose en las posibilidades de producción y la sostenibilidad de consumo. El África del siglo XX y la Europa preindustrial se utilizan para mostrar cómo esos datos pueden guiar comparaciones recíprocas para proporcionar conocimientos sobre el proceso de desarrollo en ambos continentes.